Timing of surgical antimicrobial prophylaxis: a phase 3 randomised controlled trial. Issue 6 (June 2017) - Weber, Walter P; Mujagic, Edin; Zwahlen, Marcel; Bundi, Marcel; Hoffmann, Henry; Soysal, Savas D; Kraljević, Marko; Delko, Tarik; von Strauss, Marco; Iselin, Lukas; Da Silva, Richard X Sousa; Zeindler, Jasmin; et al.
Summary: Background: Based on observational studies, administration of surgical antimicrobial prophylaxis (SAP) for the prevention of surgical site infection (SSI) is recommended within 60 min before incision. However, the precise optimum timing is unknown. This trial compared early versus late administration of SAP before surgery. Methods: In this phase 3 randomised controlled superiority trial, we included general surgery adult inpatients (age ≥18 years) at two Swiss hospitals in Basel and Aarau. Patients were randomised centrally and stratified by hospital according to a pre-existing computer-generated list in a 1:1 ratio to receive SAP early in the anaesthesia room or late in the operating room. Patients and the outcome assessment team were blinded to group assignment. SAP consisted of single-shot, intravenous infusion of 1·5 g of cefuroxime, a commonly used cephalosporin with a short half-life, over 2–5 min (combined with 500 mg metronidazole in colorectal surgery). The primary endpoint was the occurrence of SSI within 30 days of surgery. The main analyses were by intention to treat. The trial is registered withClinicalTrials.gov, numberNCT01790529 . Findings: Between Feb 21, 2013, and Aug 3, 2015, 5580 patients were randomly assigned to receive SAP early (2798 patients) or late (2782 patients). 5175 patients (2589 in the early group and 2586 in the late group) were analysed. Median administration time was 42 min before incision in the early group (IQR 30–55) and 16 min before incision in the late group (IQR 10–25). Inpatient follow-up rate was 100% (5175 of 5175 patients); outpatient 30-day follow-up rate was 88·8% (4596 of 5175), with an overall SSI rate of 5·1% (234 of 4596). Early administration of SAP did not significantly reduce the risk of SSI compared with late administration (odds ratio 0·93, 95% CI 0·72–1·21, p=0·601). Interpretation: Our findings do not support any narrowing of the 60-min window for the administration of a cephalosporin with a short half-life, thereby obviating the need for increasingly challenging SAP timing recommendations. Funding: Swiss National Science Foundation, Hospital of Aarau, University of Basel, Gottfried und Julia Bangerter-Rhyner Foundation, Hippocrate Foundation, and Nora van Meeuwen-Häfliger Foundation.